Thyrotoxic periodic paralysis as the first presentation of Graves' disease: A case report - Abdulrahman F. Al‐Mashdali (14777761) (2023)
Thyrotoxic periodic paralysis (TPP) is a rare disease seen predominantly in men of Asian origin. It should be considered in the differential diagnosis of patients with acute onset of weakness, and it is reversible after the correction of serum potassium. TPP can rarely be the initial presentation of Graves' disease. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ccr3.7188